Methodology and mathematical model with the continuous time for the selection of the optimal power of the gas turbine set for the dual fuel gas-steam combined cycle in a parallel system. (August 2018) - Bartnik, Ryszard; Buryn, Zbigniew; Hnydiuk-Stefan, Anna
Highlights: Repowering of existing thermal coal units with a gas turbine. Power optimization of the gas turbine set in the dual-fuel gas-steam unit. Economic profitability of bi-fuel gas-steam combined cycle in parallel system. Changes in the power plant value of carbon dioxide emission factor. Impact of selected parameters on the specific cost of electricity production. Abstract: Technological rationality with regard to the use of existing coal resources in power sector is based on the use of so-called clean coal technologies. One of them is the dual fuel gas-steam combined cycle technology, which couples the Joule gas turbine cycle with the Clausius-Rankine cycle of the steam turbine. Systems coupled in parallel of such units, apart from the construction of new power plants, has a large modernization potential for already existing combined heat and power plants and coal-fired power plants. Dual fuel systems may in fact be the result of a gas turbine repowering of the existing thermal coal structures. This paper presents technical and economic calculation results for various investment outlays, when the steam part works with supercritical and subcritical parameters of fresh steam, assuming different efficiency of the Clausius-Rankine cycle. Figures were obtained using innovative methodology and mathematical models of total NPV profit, discounted for the current moment achieved from the operation of the dual-fuel gas-steam power unit with a continuous time. Results are presented for a wide range of changes in prices of energy carriers and environmental charges, such as the CO2 emission allowances, including current prices level and fees.